1998
DOI: 10.2307/1349991
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Marketing Strategies Increase Net Returns for Corn and Soybean Growers

Abstract: Grain producers price grain prior to harvest to reduce financial risk and to enhance net returns. Because accomplishing the second objective is debatable, altemative com and soybean preharvest options and hedge marketing strategies were designed to test the hypothesis that preharvest pricing could generate statistically higher average net returns than harvest sales without increasing variability. Weekly seasonal futures price patterns from 1975 to 1994 were used to time marketings. The strategies were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…There is little evidence that advisory programs as a group outperform market benchmarks, particularly after considering risk. This supports the view that grain markets (cash, futures, and options) are efficient with respect to the types of marketing strategies available to farmers (e.g., Zulauf and Irwin, 1998) over the view that grain markets are inefficient and provide substantial opportunities for farmers to gain additional profits through marketing (e.g., Wisner, Blue, and Baldwin, 1998). Market advisory services (as a group) appear to have limited access to information not available to other market participants and/or mildly superior analytical skills.…”
Section: Discussionsupporting
confidence: 64%
“…There is little evidence that advisory programs as a group outperform market benchmarks, particularly after considering risk. This supports the view that grain markets (cash, futures, and options) are efficient with respect to the types of marketing strategies available to farmers (e.g., Zulauf and Irwin, 1998) over the view that grain markets are inefficient and provide substantial opportunities for farmers to gain additional profits through marketing (e.g., Wisner, Blue, and Baldwin, 1998). Market advisory services (as a group) appear to have limited access to information not available to other market participants and/or mildly superior analytical skills.…”
Section: Discussionsupporting
confidence: 64%
“…The results of the analysis also have implications for the ongoing debate about market efficiency and risk management strategies in agriculture. One view is that grain markets (cash, futures and options) are not efficient and, therefore, provide opportunities for farmers to systematically earn additional profits through marketing (e.g., Wisner, Blue and Baldwin, 1998). The other view is that grain markets are at least efficient with respect to the type of strategies available to farmers (e.g., Zulauf and Irwin, 1998).…”
Section: Performance Test Resultsmentioning
confidence: 99%
“…Wisner, Blue, and Baldwin (1998) argued that preharvest marketing strategies can increase farmers' average returns. They attributed this potential return to a yieldrisk premium.…”
Section: Futures Pricesmentioning
confidence: 99%
“…The answer remains a subject of debate. Research by Wisner et al (1998), discussed above, found that preharvest use of futures and/or options market strategies could increase average returns for corn and soybeans in relation to sales at harvest or thereafter. In a similar vane, preharvest forward contracting has been found to increase returns in relation to harvest-time sales (e.g., Kolajo, Hurst, & Martin, 1988).…”
Section: Performance Of Marketing Strategiesmentioning
confidence: 99%